2008
DOI: 10.1093/intqhc/mzn038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of overridden alerts in a drug-drug interaction detection system

Abstract: We created a classification of overridden alerts, in the context of computerized physician order entry system coupled with a drug-drug interaction detection system. There is clearly room for improvement in the development of drug-drug interaction software. This classification should make it possible to break this work down into smaller tasks, making it possible to decrease the sensitivity to background noise of drug-drug interaction detection systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
1
17
0
12
Order By: Relevance
“…current literature that recognises the importance of alert presentation and its effect on workflow. [7][8][9] These themes will be explored further to ensure that system design is in line with expectations.…”
Section: Discussionmentioning
confidence: 99%
“…current literature that recognises the importance of alert presentation and its effect on workflow. [7][8][9] These themes will be explored further to ensure that system design is in line with expectations.…”
Section: Discussionmentioning
confidence: 99%
“…We also decided to introduce drugs classified as relevant and potentially dangerous by the bibliography to avoid alert fatigue. In real practice there are many publications which show that the alerts are not always successful in fulfilling their purpose and do not reduce medication errors 24. The most common cause of this failure is that many clinicians ignore the warnings because they become excessive or difficult to find or understand 25.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the system used was not designed for paediatric use, and it had many drug duplicate alerts overridden due to limitations in complex or variable dosing patterns 33. A paediatric study on drug–drug interaction alerts found that 69% of these were overridden, and of these, 45% were informational or system errors, as the system lacked the ability to recognise real interactions and conflicted with guidelines that stated the drugs could be used together 32. A third study tested dosing suggestion alerts where the top 200 paediatric drugs had dosing rules attached for their most common indication 34.…”
Section: Handling Of Cdss Alertsmentioning
confidence: 99%